Lagunas de estabilización para el tratamiento de las aguas residuales de la ciudad de Junín y la calidad ambiental del área intersectada - Bravo, Carlina Monserrate (2013)
The purpose of this paper is to evaluate and monitor the current behavior of stabilization ponds used for the treatment of domestic sewage in the municipality of Junín, through the quantitative method, the same operation identified gaps, as the possible effects that may affect the environmental quality of the area of intersection. So performance determining the lagoons is inadequate and deficient so that environmental quality is impaired in its components water, air and soil, and in order to improve the treatment of municipal wastewater, to minimize environmental impacts developed an environmentalmanagementprogramme.